STROBE-compliant integrin through focal adhesion involve in cancer stem cell and multidrug resistance of ovarian cancer. Issue 12 (March 2017) - Wei, Luwei; Yin, Fuqiang; Zhang, Wei; Li, Li
Abstract : Abstract: Cancer stem cells (CSCs) are considered to be the root of carcinoma relapse and drug resistance in ovarian cancer. Hunting for the potential CSC genes and explain their functions would be a feasible strategy to meet the challenge of the drug resistance in ovarian cancer. In this study, we performed bioinformatic approaches such as biochip data extraction and pathway enrichment analyses to elucidate the mechanism of the CSC genes in regulation of drug resistance. Potential key genes, integrins, were identified to be related to CSC in addition to their associations with drug resistance and prognosis in ovarian cancer. A total of 36 ovarian CSC genes involved in regulation of drug resistance were summarized, and potential drug resistance-related CSC genes were identified based on 3 independent microarrays retrieved from the Gene Expression Omnibus (GEO) Profiles. Pathway enrichment of CSC genes associated with drug resistance in ovarian cancer indicated that focal adhesion signaling might play important roles in CSC genes-mediated drug resistance. Integrins are members of the adhesion molecules family, and integrin subunit alpha 1, integrin subunit alpha 5, and integrin subunit alpha 6 (ITGA6) were identified as central CSC genes and their expression in side population cells, cisplatin-resistant SKOV3 (SKOV3/DDP2) cells, and cisplatin-resistant A2780 (A2780/DDP) cells were dysregulated as measured by real-time quantitative polymerase chain reaction. The high expression of ITGA6 in 287 ovarian cancer patients of TCGA cohort was significantly associated with poorer progression-free survival. This study provide the basis for further understanding of CSC genes in regulation of drug resistance in ovarian cancer, and integrins could be a potential biomarker for prognosis of ovarian cancer.